Relevant Affect Factors of Smartphone Mobile Data Traffic - Husnjak, Siniša; Peraković, Dragan; Cvitić, Ivan (Promet - Traffic&Transportation, 2016)
Smartphones are used to access a wide range of different information and communication services and perform functions based on data transfer. A number of subscription contracts for smartphones is rapidly increasing, and the development of mobile communications network provides higher speed of data transfer. The continuous increase in the average amount of data traffic per one subscriber contract leads to an increase in the total Mobile Data Traffic (MDT), globally. This research represents a summary of factors that affect the amount of smartphone MDT. Previous literature shows only a few of the factors individually that affect the realization of smartphone MDT. The results of the research clarify the ways which influence the amount of MDT generated by a smartphone. This paper increases the awareness of the users of the methods of generating smartphone MDT. The research also allows users to specify parameters that affect the prediction of generated MDT of a smartphone.